1976
DOI: 10.3758/bf03337269
|View full text |Cite
|
Sign up to set email alerts
|

The locus of stimulus probability effect in choice reaction time

Abstract: A choice reaction time experiment was conducted in which subjects were to respond with one response to either of two stimuli, S1 and S2, and with another response to a third stimulus, S3. The stimuli in the low-compatibility condition were three colors and the responses were letter names. In a high-compatibility condition, S1 and 82 were upper-and lowercases of the same letter and S3 was another letter. The responses were the letter names. The relative frequency of S1 and S2 was manipulated. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Within the larger context of the entire information processing system, stimulus probability is emerging as a variable whose influence is seen at many stages. It has been shown that probability has a larger effect when stimulus-response compatibility is low, for example, indicating an effect of probability on some phase of response selection as well as on perceptual mechanisms (Hawkins et al, 1973;Spector & Lyons, 1976). In view of this diversity of established probability effects, it seems inevitable that any complete model for probability effects must address multiple processing stages.…”
Section: Resultsmentioning
confidence: 99%
“…Within the larger context of the entire information processing system, stimulus probability is emerging as a variable whose influence is seen at many stages. It has been shown that probability has a larger effect when stimulus-response compatibility is low, for example, indicating an effect of probability on some phase of response selection as well as on perceptual mechanisms (Hawkins et al, 1973;Spector & Lyons, 1976). In view of this diversity of established probability effects, it seems inevitable that any complete model for probability effects must address multiple processing stages.…”
Section: Resultsmentioning
confidence: 99%
“…Despite considerable research into this possibility, however, there is still disagreement about whether perceptual adjustments do in fact contribute to the probability effect (e.g., Blackman, 1972;F. De Jong & Sanders, 1986;Dykes & Pascal, 1981;Gescheider, Wright, Weber, Kirchner, & Milligan, 1969;Miller & Pachella, 1973;Orenstein, 1970;Sanders, 1977Sanders, , 1980Spector & Lyons, 1976). Effects of perceptual manipulations like stimulus intensity and stimulus discriminability sometimes have no larger effects for low-probability stimuli than for high-probability ones, contrary to what would be expected if probability affected the rate of perceptual processing.…”
mentioning
confidence: 99%
“…This finding suggests that probability influences the time required by perceptual processes to recognize a stimulus. Similarly, the effect of S-R compatibility is generally larger for low-probability stimuli than for high-probability stimuli (e.g., Hawkins et al, 1973;Sanders, 1970;Spector & Lyons, 1976), suggesting that probability also affects the time needed for response selection. Indeed, Blackman (1975) obtained interactions of probability with both stimulus quality and S-R compatibility in a single experiment, although these variables were additive with each other.…”
mentioning
confidence: 99%